2019
DOI: 10.1111/ijcp.13426
|View full text |Cite
|
Sign up to set email alerts
|

Expert consensus on the management of hypertension in the young and middle‐aged Chinese population

Abstract: Summary Background and purposeThe increased prevalence of hypertension, along with obesity, dyslipidemia, and type 2 diabetes in the young and middle‐aged population has become a major global public health issue. Although more attention has been paid to the management of hypertension and cardiovascular disease (CVD) risks in elderly patients nationally and internationally, there is currently no consensus worldwide on appropriate evaluation and treatment of hypertension in younger subjects. We developed the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…Lower cut-off values of LAP in younger age subgroups may indicate that lipid over accumulation has a greater impact on hypertension risk in younger subjects than in older subjects. This finding is in accordance with data that showed that the pathophysiology of hypertension in young and middle-aged adults differs from that in elderly subjects and tends to be associated with metabolic disorders 19 . Whereas, the age-associated increase in large-artery stiffness is the main characteristic of arterial hypertension in elderly individuals 20 .…”
Section: Discussionsupporting
confidence: 93%
“…Lower cut-off values of LAP in younger age subgroups may indicate that lipid over accumulation has a greater impact on hypertension risk in younger subjects than in older subjects. This finding is in accordance with data that showed that the pathophysiology of hypertension in young and middle-aged adults differs from that in elderly subjects and tends to be associated with metabolic disorders 19 . Whereas, the age-associated increase in large-artery stiffness is the main characteristic of arterial hypertension in elderly individuals 20 .…”
Section: Discussionsupporting
confidence: 93%
“…There are unmet needs for providing healthcare professionals with a tailored hypertension management strategy in this special population. An expert consensus has been developed and published recently to meet the unmet needs [17].…”
Section: Discussionmentioning
confidence: 99%
“…The drugs used in NARRAS trial were in keeping with current guidelines and consensus recommendations ( 19 22 ). Long-acting CCBs, amlodipine or nifedipine GITS, both provide sustained 24-h BP control.…”
Section: Discussionmentioning
confidence: 99%